MUSICIAN-PROFESSOR: A COMPLEX MATTER - Marisa Fonterrada, Scheilla Glaser e (2007)
The following article develops considerations of both piano teaching and the education of the music teacher in São Paulo, Brazil. It shows the results of a research concluded in 2005 that had as its starting point pedagogic assumptions present in music programs. The research was based on the theory of Systemic Thought, by Vasconcellos (2002) and on Carl Rogers’ study of the student-centered teaching. The methodology applied was particularized to each analyzed segment, using Fachin’s method definition (2002). Keywords: Piano teaching; Musician/teacher; Carl Rogers; Significant learning.